The Effectiveness of An Android-Based Quitee Educational Game on Adolescents’ Motivation and Oral Health Knowledge - Sari Aldilawati; Muhammad Jayadi Abdi; Muhammad Sandikal (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Oral and dental health problems remain a major public health concern, particularly among adolescents. Based on the Indonesian Health Survey (SKI) 2023, dental caries prevalence among children aged 10–14 years reached 37.2%. Adolescents are vulnerable due to behavioral changes and limited awareness of oral hygiene. Knowledge and motivation are important factors in promoting healthy behaviors. Therefore, interactive technology-based media, such as digital games, may be an effective educational approach. Materials and Methods: This study aimed to evaluate the effectiveness of the Android-based Quitee educational game in improving adolescents’ oral health knowledge and motivation. A pre-experimental one-group pretest-posttest design was conducted among 158 students of SMP Negeri 29 Makassar, selected using purposive sampling. Data were collected using validated questionnaires consisting of 10 knowledge and 10 motivation items, scored 1 for correct and 0 for incorrect responses. Results and Discussion: Following the intervention, motivation scores increased from 5.00 to 8.08, while knowledge scores increased from 5.59 to 8.10. Both improvements were statistically significant (p < 0.001). The findings indicate that Quitee effectively improved adolescents’ oral health knowledge and motivation, with a greater effect observed on motivation. Conclusion: The Android-based Quitee educational game is a promising digital medium for improving oral health knowledge and motivation among adolescents.